LiBF4‐Induced Rearrangement and Desymmetrization of a Palladium‐Ligand Assembly. (13th April 2022) - Sudan, Sylvain; Fadaei‐Tirani, Farzaneh; Scopelliti, Rosario; Ebbert, Kristina E.; Clever, Guido H.; Severin, Kay
Abstract: Thirteen palladium‐ligand assemblies with different structures and topologies were investigated for the ability to bind lithium ions. In one case, the addition of LiBF4 resulted in a profound structural rearrangement, converting a dincluclear [Pd2 L4 ] 4+ complex into a low‐symmetry [Pd4 L8 ] 8+ assembly with two binding pockets for solvated LiBF4 ion pairs. The rearrangement could only be induced by Li +, indicating highly specific host–guest interactions. A structural analysis of the [Pd4 L8 ] 8+ receptor revealed a compact structure with multiple intramolecular interactions, reminiscent of what is seen for natural and synthetic foldamers. Abstract : Template‐induced complexity: LiBF4 induces the rearrangement of a homoleptic Pd2 L4 complex into a Pd4 L8 assembly. The complex shows a folded, highly compact structure, with a low apparent symmetry and two highly specific binding pockets.